ANALYSIS OF THE PRESENTATION OF FINANCIAL REPORTS OF SERDANG BEDAGAI REGENCY IN 2024 - Manihuruk, Eloy Fita; Ivana Limbong, Marhsya Prita; Muda, Iskandar (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2025)
Financial reporting in the public sector is a key element of good governance, promoting transparency, accountability, and effici ent management of public resources. Local governments, including Serdang Bedagai Regency in Indonesia, bear the responsibility to pre pare reports that accurately reflect their financial position, perform ance, and cash flows. These reports are vital for internal decision-making and serve as a main source of information for external stakeh olders such as citizens, legislators, auditors, and development partn ers. The quality of financial reporting directly influences the ability of stakeholders to assess performance, monitor public funds, and hold officials accountable. Located in North Sumatra Province, Serdang Bedagai Regency continues to strengthen its financial report ing practices. Its 2024 financial reports are particularly important as they reflect efforts to meet public demands and regulatory requir ements. This study analyzes the regency’s 2024 reports, focusing on compliance with SAP, clarity of information, accessibility, and effectiveness, while incorporating financial indicators and self-reliance ratios to evaluate fiscal health and governance quality.